Is Hybrid Telehealth Model the Next Step for Private Healthcare in India? - Anjali Raj Westwood (Health Services Insights, 2021)
Irrespective of geography, the implementation of telehealth has been one of the biggest changes caused by the COVID-19 pandemic. Post the pandemic, telehealth will continue to be part of mainstream health service delivery but in a different format. This commentary investigates the hybrid model of telehealth in India. A hybrid model can help India provide accessible and affordable healthcare to a wider part of its population and support the already growing medical tourism industry. The challenges to this revolve around digital education for patients and providers, integration of technology into existing care pathways, infrastructural investment and in creating seamless systems. It is a scalable and profitable model that must be seriously considered in the post pandemic world.
Keywords: Telehealth; Service delivery; Health policy; India